The inc-dec game and how to mitigate it - Pär Holmberg (Research Institute of Industrial Economics (IFN), 2024)
The power exchange and the real-time markets used by the system operator differ in how system constraints are managed. This can result in regulatory arbitrage, which can increase consumer costs, increase the risk of power outages and distort investment incentives. This paper uses a game-theoretical approach to study these problems and proposes various measures to reduce them. For example, zones and grid tariffs can be adjusted. Moreover, regulations of real-time markets can improve, and transmission system operators can implement measures to increase the capacity of the existing grid.
Keywords: C72; D47; L94; 330; Congestion management; zonal pricing; countertrading; redispatch; real-time market; regulatory arbitrage; inc-dec game